Great Canadian Lagerstätten 1. Early Eocene Lagerstätten of the Okanagan Highlands (British Columbia and Washington State) - Archibald, S.; Greenwood, David; Smith, Robin; Mathewes, Rolf; Basinger, James (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2011)
SUMMARY The Early Eocene Okanagan High lands series of lacustrine shale and coal deposits, in far western North Ameri ca, constitutes a significant group of fossil sites with exceptional preserva tion of a diverse suite of organisms (Lagerstätten). With contemporaneous basins arrayed across about 1000 kilo metres of southern British Columbia and northern Washington, these sites offer a unique opportunity to examine the paleoecology of terrestrial commu nities spanning a temperate, low-sea sonality landscape in a montane setting during a time of generally warm tem peratures across the globe. The Okana gan Highlands sites provide an unpar alleled comparative framework within which to examine this major turning point in terrestrial community develop ment during the emergence of their broad modern character.